ANALYSIS OF CRIMINAL SANCTIONS FOR PEOPLE OF ANIMAL ABUSE: ANALISIS SANKSI PIDANA BAGI MASYARAKAT PENYALAHGUNAAN HEWAN - Ismawati Septiningsih (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The old Indonesian Criminal Code, which is a translation of Wetboek van Strafrecht for Nederlandsch Indie, has provided regulations regarding the abuse of animals. However, so far there are still many cases of animal abuse, because people consider this act to be trivial and the criminal sanctions are not too severe. The aim of writing this article is to find out appropriate and strict rules to prevent animal abuse. This article was written using a normative legal research method with a statutory approach. The results of this research are that regulations regarding animal abuse should be equipped with more specific regulations and heavier sanctions so that they can run effectively.